Data Communications and Network Technologies - Huawei Technologies Co., Ltd (Springer Nature, 2023)
This open access book is written according to the examination outline for Huawei HCIA-Routing Switching V2.5 certification, aiming to help readers master the basics of network communications and use Huawei network devices to set up enterprise LANs and WANs, wired networks, and wireless networks, ensure network security for enterprises, and grasp cutting-edge computer network technologies. The content of this book includes: network communication fundamentals, TCP/IP protocol, Huawei VRP operating system, IP addresses and subnetting, static and dynamic routing, Ethernet networking technology, ACL and AAA, network address translation, DHCP server, WLAN, IPv6, WAN PPP and PPPoE protocol, typical networking architecture and design cases of campus networks, SNMP protocol used by network management, operation and maintenance, network time protocol NTP, SND and NFV, programming, and automation. As the world's leading provider of ICT (information and communication technology) infrastructure and smart terminals, Huawei's products range from digital data communication, cyber security, wireless technology, data storage, cloud-computing, and smart computing to artificial intelligence.